2018
DOI: 10.1007/s13280-018-1052-9
|View full text |Cite
|
Sign up to set email alerts
|

Lead poisoning and other human-related factors cause significant mortality in white-tailed eagles

Abstract: The white-tailed eagle (Haliaeetus albicilla) suffered a severe population decline due to environmental pollutants in the Baltic Sea area ca. 50 years ago but has since been recovering. The main threats for the white-tailed eagle in Finland are now often related to human activities. We examined the human impact on the white-tailed eagle by determining mortality factors of 123 carcasses collected during 2000-2014. Routine necropsy with chemical analyses for lead and mercury were done on all carcasses. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
1
24
0
4
Order By: Relevance
“…Isotope analysis was consistent with lead ammunitionIshii et al (2017)Poland7 of 22 birds found dead or moribund had liver lead levels > 30 ppm dw, two of which were 180.3 and 188.6 ppm dw. This was apparently associated with feeding on wintering waterfowl and carrionKitowski et al (2017a)FinlandLead poisoning was the most important cause of human-related mortality in 123 carcasses of white-tailed eagles (collected 2000–2014) accounting for 31% of all casesIsomursu et al (2018)IrelandA white-tailed eagle at Lough Derg died of lead poisoning believed to be associated with the bird feeding on wildfowl that had been shot with lead shotO’Donoghue (2017)Bald eagle Haliaeetus leucocephalus USA—Upper Mississippi River ValleyPbB was higher immediately following the hunting season and lower when the previous months’ snowfall was greater than 11 cm, when game animal carcasses may be concealedLindblom et al (2017)16.3% of 2980 bald eagle deaths between 1975 and 2013 were from lead poisoning. The proportion of lead-poisoned eagles increased in all 4 migratory bird flyways of the United States after the autumn 1991 ban on the use of lead shot for waterfowl hunting, probably as Bald Eagles consume lead ammunition fragments (from bullets) in offal and carcasses left behind during big game hunting seasonsRussell and Franson (2014)USA—Iowa31% of 209 eagles brought to rehabilitation centres (2004-2014) had PbB > 60 µg/dl.…”
Section: Pathways Of Exposurementioning
confidence: 99%
“…Isotope analysis was consistent with lead ammunitionIshii et al (2017)Poland7 of 22 birds found dead or moribund had liver lead levels > 30 ppm dw, two of which were 180.3 and 188.6 ppm dw. This was apparently associated with feeding on wintering waterfowl and carrionKitowski et al (2017a)FinlandLead poisoning was the most important cause of human-related mortality in 123 carcasses of white-tailed eagles (collected 2000–2014) accounting for 31% of all casesIsomursu et al (2018)IrelandA white-tailed eagle at Lough Derg died of lead poisoning believed to be associated with the bird feeding on wildfowl that had been shot with lead shotO’Donoghue (2017)Bald eagle Haliaeetus leucocephalus USA—Upper Mississippi River ValleyPbB was higher immediately following the hunting season and lower when the previous months’ snowfall was greater than 11 cm, when game animal carcasses may be concealedLindblom et al (2017)16.3% of 2980 bald eagle deaths between 1975 and 2013 were from lead poisoning. The proportion of lead-poisoned eagles increased in all 4 migratory bird flyways of the United States after the autumn 1991 ban on the use of lead shot for waterfowl hunting, probably as Bald Eagles consume lead ammunition fragments (from bullets) in offal and carcasses left behind during big game hunting seasonsRussell and Franson (2014)USA—Iowa31% of 209 eagles brought to rehabilitation centres (2004-2014) had PbB > 60 µg/dl.…”
Section: Pathways Of Exposurementioning
confidence: 99%
“…Lead (Pb) is a naturally occurring but nonessential element that is highly toxic at elevated concentrations and with a potential to affect most body systems in animals. Exposure to Pb and incidences of Pb poisoning have been extensively reported for several diurnal birds of prey around the world, notably eagles and vultures (Wayland and Bollinger 1999; Kurosawa 2000; Church et al 2006; Pattee et al 2006; Krone et al 2009; Franson and Russel 2014; Berny et al 2015; Mateo-Tomás et al 2016; Ecke et al 2017; Wiemeyer et al 2017; Isomurso et al 2018), and scarcely for the mainly nocturnal Eurasian eagle owl Bubo bubo (Mateo et al 2003, Kim and Oh 2012) and great horned owl Bubo virginianus (Clark and Scheuhammer 2003). Mortality from Pb poisoning in birds is mostly associated with ingestion of lead-shot or bullet fragments of hunting ammunition and associated with feeding habits occurring mainly in various ducks and raptorial birds (summarized in Franson and Pain 2011).…”
mentioning
confidence: 99%
“…Na necropsia, é possível detectar alterações na morfologia hepática, aumento de vesícula biliar, ductos biliares dilatados, refluxo da bile para ventrículo, essas alterações não são patognomônicas, mas sim indicativas de intoxicação por chumbo (Krone, 2018). Em um estudo realizado por Isomursu et al (2018), as alterações de vesícula biliar aumentada e bile viscosa com coloração verde escura foram encontradas em 97% dos casos de intoxicação por chumbo. Romero et al (2019) relacionam a ingestão de Pb com a coloração verde escura da mucosa do ventrículo de aves.…”
Section: Ingestão Do Chumbo Sinais Clínicos E Patologiaunclassified
“…O diagnóstico de intoxicação pode ser feito através da dosagem de Pb em rins e fígado, com nível maior que 5 mg/kg. A concentração média de chumbo nestes tecidos, na espécie Haliaeetus albicilla, foram de 9,2 mg/kg e 18,7 mg/kg, na devida ordem (Isomursu, et al, 2018). Ao empregar gaivotas como referência, Vizuete et al (2018), dosaram o chumbo nas espécies L. argentatus da Itália e L. ridibundus da Polônia, e obtiveram resultados em tecido hepático de <0,1 a 8,91 ± 1.87 μg/g, respectivamente.…”
Section: Amostras E Biomarcadores De Chumbounclassified